Serotonin 5-HT2A receptor expression is chronically decreased in the anterior cerebral cortex of male rats following repetitive low-level blast exposure - Rita De Gasperi; Rita De Gasperi; Georgina Perez Garcia; Georgina Perez Garcia; Miguel A. Gama Sosa; Miguel A. Gama Sosa; Gissel M. Perez; Rania Abutarboush; Rania Abutarboush; Usmah Kawoos; Usmah Kawoos; Patrick R. Hof; et al. (Frontiers in Neurology, 2025)
IntroductionMany Veterans who experienced blast-related traumatic brain injuries (TBIs) in Iraq and Afghanistan currently suffer from chronic cognitive and mental health problems that include depression and post-traumatic stress disorder (PTSD). Male rats exposed to repetitive low-level blast develop chronic cognitive and PTSD-related behavioral traits that are present for more than 1 year after exposure. Psychedelic agents alter cognition as well as mood and agents such as psilocybin have gained attention as possible treatments for the mental health disorders that affect Veterans. The best-known action of psilocybin’s metabolite psilocin is to stimulate the serotonin 2A receptor (5-HT2AR). The aim of this study was to determine whether 5-HT2AR levels are altered by blast exposure.Methods5-HT2AR expression was examined by Western blot in 7 cohorts of rats exposed to low level repetitive blast collected from 2 weeks to 12 months after blast exposure. The analysis included three brain regions (anterior cerebral cortex, hippocampus and amygdala) that were chosen based on being relevant to fear learning and the biological basis of PTSD. Possible correlations between Western blot data and behavioral outcomes were evaluated.Results5-HT2AR was chronically decreased in anterior cortex of blast-exposed rats in all cohorts except the one studied at 2 weeks after blast exposure. 5-HT2AR levels were variably affected in the other regions. 5-HT2AR expression correlated differently in blast and control rats in some behavioral parameters.ConclusionThese findings have implications for understanding the neurochemical basis of blast-induced cognitive and behavioral changes. They also suggest 5-HT2AR as a potential therapeutic target for treatment of PTSD-related symptoms that follow blast injury.